Transforming Shame in the Pandemic: An International Study - Mayer, Claude-Hélène; Vanderheiden, Elisabeth (Frontiers in Psychology, 2021)
Shame is an unconscious, somewhat unattended and neglected emotion and occurs when individual and socio-cultural norms are violated. It often impacts negatively on the self and others across cultures. During the Covid-19 crises, shame has become an important emotion with a powerful effect, depending on how it is experienced within the socio-cultural context. This article explores shame in international perspectives in the context of Covid-19 and addresses the question how shame is transformed from an existential positive psychology (PP2.0) perspective. The study uses a qualitative research paradigm and explores shame and its transformation during Covid-19. Purposeful and snowball sampling was used. The sample consisted of 24 individuals (16 female, 8 male), of 13 different nationalities. Data were collected from written interviews and analyzed through thematic analysis. Ethical considerations were followed; ethical approval was given by a university. Findings show that participants become very worried, anxious, scared, sad and shocked when they or individuals in their close relationships contracted Covid-19. Shame plays an important role during the Covid-19 pandemic. However, the meaning and experience of shame during Covid-19 is strongly dependent on the socio-cultural background of the individual who is experiencing the disease. Individuals use different strategies and mechanisms to deal with and transform shame in the context of Covid-19. Findings are presented, conclusions are drawn and recommendations for future research and practice are given.